Redeeming the Acquired Virtues - Herdt, Jennifer A. (Journal of religious ethics, 2013)
The probing readings of Putting On Virtue offered by Sheryl Overmyer, Darlene Weaver, and James Foster provide a welcome opportunity for further reflection on key questions: Was Aquinas really concerned with the status of pagan virtues? Can we properly understand a thinker whose driving questions are not the same as our own without taking up a stance of pure deference? Can an inquiry into hyper-Augustinian anxiety over acquired virtue assist us in arriving at an account of positive self-regard? Can an account that stresses the graced character of all virtue formation be coherent? And can it do justice to the ways in which Christians reached for accounts of infused virtue precisely in order to affirm how grace overcomes the ways in which fortune hounds acquired virtue? I respond affirmatively to all of the above.